Aß aggregation and possible implications in Alzheimer's disease pathogenesis - Bharadwaj, Prashant; Dubey, A.; Masters, C.; Martins, R.; Macreadie, I. (2009)
Amyloid ß protein (Aß) has been associated with Alzheimer's disease (AD) because it is a major component of the extracellular plaque found in AD brains. Increased Aß levels correlate with the cognitive decline observed in AD. Sporadic AD cases are thought to be chiefly associated with lack of Aß clearance from the brain, unlike familial AD which shows increased Aß production. Aß aggregation leading to deposition is an essential event in AD. However, the factors involved in Aß aggregation and accumulation in sporadic AD have not been completely characterized. This review summarizes studies that have examined the factors that affect Aß aggregation and toxicity. By necessity these are studies that are performed with recombinant-derived or chemically synthesized Aß. The studies therefore are not done in animals but in cell culture, which includes neuronal cells, other mammalian cells and, in some cases, non-mammalian cells that also appear susceptible to Aß toxicity. An understanding of Aß oligomerization may lead to better strategies to prevent AD. © 2009 CSIRO.